The effect of capital structure on stock prices with profitability as an intervening variable in mining sector companies listed on the Indonesian stock exchange for the 2020-2024 period - Lailatul Uyun; Fitriah Fitriah (Institute of Accounting Research and Novation (IARN), 2025)
This research aimed to investigate whether capital structure affects stock prices, with Profitability as an intervening variable, in the mining sector listed on the Indonesian Stock Exchange from 2002 to 2024. In this research, capital structure is measured by the debt-to-equity ratio, and the return on equity measures Profitability. The population used in this research, listed on the Indonesia Stock Exchange for the 2020-2024 period, is from the mining sector. The research sample consisted of 26 companies from a total population of 43. Sampling used purposive sampling. The analysis methods used in this study include classical assumption tests, partial tests (t-tests), path analysis, and the Sobel test for mediation analysis. The result of this research showed that: (1) Capital structure has a negative and insignificant effect on stock prices, (2) Capital structure has a negative and insignificant effect on Profitability, (3) Profitability has a positive and significant effect on stock prices, (4) Profitability can mediate the relationship between capital structure and stock prices.